Histamine and diabetic nephropathy: an up-to-date overview. (3rd January 2019) - Pini, Alessandro; Verta, Roberta; Grange, Cristina; Gurrieri, Maura; Rosa, Arianna Carolina
Abstract : The classification of diabetic nephropathy (DN) as a vascular complication of diabetes makes the possible involvement of histamine, an endogenous amine that is well known for its vasoactive properties, an interesting topic for study. The aim of the present review is to provide an extensive overview of the possible involvement of histamine in the onset and progression of DN. The evidence collected on the role of histamine in kidney function together with its well-known pleiotropic action suggest that this amine may act simultaneously on glomerular hyperfiltration, tubular inflammation, fibrosis development and tubular hypertrophy.